2021
DOI: 10.1016/j.idcr.2021.e01130
|View full text |Cite
|
Sign up to set email alerts
|

Renal abscesses and endogenous endophthalmitis due to hypermucoviscous hypervirulent Klebsiella pneumoniae (HVKP)

Abstract: We describe a diabetic patient with left eye endogenous endophthalmitis due to hypervirulent hypermucoviscous Klebsiella pneumoniae (HKVP) originating from right renal abscesses. A rare source of HVKP causing endogenous endophthalmitis. Despite treatment with intravenous ceftazidime and pars plana vitrectomy, the patient required evisceration of the left eye. A high index of suspicion for endogenous endophthalmitis and awareness of the virulence and potential antibiotic resistance of HVK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The median number of administrations in the reviewed studies was 3–5 [ 12 , 58 , 67 , 77 ]. However, Martel successfully treated a Kp subretinal abscess with intensive intravitreal ceftazidime and vancomycin, daily for one week, then at 48 h, with a total of 13 administrations [ 80 ].…”
Section: Management Of Ekementioning
confidence: 99%
See 2 more Smart Citations
“…The median number of administrations in the reviewed studies was 3–5 [ 12 , 58 , 67 , 77 ]. However, Martel successfully treated a Kp subretinal abscess with intensive intravitreal ceftazidime and vancomycin, daily for one week, then at 48 h, with a total of 13 administrations [ 80 ].…”
Section: Management Of Ekementioning
confidence: 99%
“…However, Ang et al found that early vitrectomy is not associated with a better visual outcome [ 16 ]. Martel et al raised concern about the efficacy and results of PPV on an inflamed necrotic retina [ 80 ]. A vitrectomy could result in supplementary damage of the retina, especially if the vitreous body is not detached due to vitreoretinal tractions.…”
Section: Management Of Ekementioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic patients with K. pneumoniae hepatobiliary infections have a higher risk of developing endogenous K. pneumoniae endophthalmitis (EKE) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. EKE has been found in patients with other infections, such as pneumonia and renal abscess [ 8 , 9 , 10 , 11 ]. K. pneumoniae isolates are typically susceptible to ceftazidime and amikacin, which are currently used empirically to treat endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%